Implementation of a Regional STEMI Network in North Cairo (Egypt): Impact on The Management and Outcome of STEMI Patients - Sameh M. Shaheen; Atef K. Saleh; Nireen K. Okasha; Mohammed A. Abdalhamid; Hany M. Fakhry; Ramez R. Guindy (Ubiquity Press, 2023)
Background: Regional ST-segment-elevation myocardial infarction (STEMI) networks facilitate timely performance of primary percutaneous coronary intervention (PPCI), reduce mortality and improve outcomes. Few data exist on the feasibility and impact of regional STEMI networks in developing countries. Aim of the Work: The aim of this study was to examine the feasibility and impact of establishing a regional STEMI network on the management and outcomes of STEMI patients in north Cairo. Patients and Methods: A prospective observational study conducted on 352 patients presenting in North Cairo with confirmed diagnosis of STEMI within 48 hours of symptoms. Patients were divided into group I (n = 140) before and group II (n = 212) after establishment of the STEMI network. Both groups were compared as regards patients' demographics, presentation, management and short-term outcomes. The north Cairo regional STEMI network was established among four governmental hospitals and the governmental ambulance was used for interhospital transfer. WhatsApp® was used for trans-network team communication. Results: Mean age of the study population was 55.4 ± 11.02 years and 286 (81.3%) were males. Mean time from chest pain to first medical contact did not change between the two groups (240 minutes; P = 0.36) while door to balloon mean time was reduced (from 54.3 to 44.1 minutes: P = 0.01). Use of thrombolytic therapy declined from 51 (36.4%) to 16 (7.5%) (P < 0.001) while primary PCI increased from 59.8% to 77.1% (p < 0.001). Left ventricular ejection fraction improved from 51.3 ± 10.7 to 55.4 ± 9.1 (P < 0.001), the mean time of CCU stay was reduced from a mean of 3.0 to 2.0 days (P < 0.001) and in-hospital mortality improved from 6.4% to 2.8% (P = 0.10). Conclusion: The establishment of the STEMI network in north Cairo was feasible and improved patients' outcomes. Use of primary PCI increased and in-hospital mortality improved from after establishment of STEMI network.